A Pathway From Porous Particle Technology Toward Tailoring Aerogels for Pulmonary Drug Administration - Duong, Thoa; López-Iglesias, Clara; Szewczyk, Piotr K.; Stachewicz, Urszula; Barros, Joana; Alvarez-Lorenzo, Carmen; Alnaief, Mohammad; García-González, Carlos A. (Frontiers in Bioengineering and Biotechnology, 2021)
Pulmonary drug delivery has recognized benefits for both local and systemic treatments. Dry powder inhalers (DPIs) are convenient, portable and environmentally friendly devices, becoming an optimal choice for patients. The tailoring of novel formulations for DPIs, namely in the form of porous particles, is stimulating in the pharmaceutical research area to improve delivery efficiency. Suitable powder technological approaches are being sought to design such formulations. Namely, aerogel powders are nanostructured porous particles with particularly attractive properties (large surface area, excellent aerodynamic properties and high fluid uptake capacity) for these purposes. In this review, the most recent development on powder technologies used for the processing of particulate porous carriers are described via updated examples and critically discussed. A special focus will be devoted to the most recent advances and uses of aerogel technology to obtain porous particles with advanced performance in pulmonary delivery.